Communication audit. - Chen, Harn Shuian. (2008)
For this report, we aim to carry out a demonstration of communication audit. This is to obtain more information regarding the strengths and weaknesses of the internal communication of the organization, to formulate better strategies to improve on the effectiveness of communication, which ultimately helps to improve organizational effectiveness, so as to drive work performance.